(untitled) (Itinera, 2019)
This study examines two examples of theatrical performances that create potential dramaturgies by constructing multiple narratives. In his “in kit” works French director Philippe Quesne establishes a “parliament” of things where the spectators can marvel at the surrounding world, while in the joyful theatre of the Flemish company De KOE multiple fictions are capable of reinventing, or even re-enchanting our present.